Effort During Ethanol Breath Testing Impacts Correlation with Serum Ethanol Concentration - Samuel J. Stellpflug; William H. Menton; Bjorn C. Westgard; Ryan D. Johnsen; Alexander M. Coomes; Robert C. LeFevere; Michael D. Zwank (Western Journal of Emergency Medicine)
Introduction: The gold standard for quantifying ethanol intoxication in patients is serum testing. However, breath testing is faster, less expensive, and less invasive. It is unknown whether perceived effort during a breath ethanol test impacts the accuracy of the test and the correlation with serum concentration. In this study we analyzed whether perceived “poor” effort during breath ethanol testing would result in worse correlation than perceived “normal” breath-testing effort with respect to serum ethanol concentration. Methods: Subjects were identified retrospectively over a 49-month period if they had both a breath ethanol test and a serum ethanol test obtained during the same ED visit within 60 minutes of each other, if they had their effort during the breath test recorded as “normal” or “poor” by the person administering the test, and had non-zero breath and serum ethanol concentrations. We completed descriptive and correlation analyses. Results: A total of 480 patients were enrolled, 245 with normal and 235 with poor effort. The patients with normal breath-test effort had mean breath and serum concentrations of 0.19 grams per deciliter (g/dL) and 0.23 g/dL, respectively. The patients with poor breath-test effort had mean breath and serum concentrations of 0.19 and 0.29 g/dL, respectively. The correlation coefficient between breath and serum ethanol values was 0.92 (95% confidence interval (CI) 0.84–0.96) for good effort and 0.63 (95% CI 0.53–0.74) for poor effort. Conclusion: The assessment of breath exhalation effort is meaningful in determining how well a patient’s breath ethanol level correlates with the serum ethanol concentration. Poor breath effort, when compared to normal breath effort, was associated with higher ethanol levels as well as a larger difference and a greater variability between breath and serum values. If an accurate ethanol level is important for clinical decision-making, a physician should not rely on a poor-effort breathalyzer value.